Prevalence and pattern of domestic violence at the Center for Forensic Medical Services in Pekanbaru, Indonesia (Faculty of Medicine Universitas Indonesia, 2017)
Background: Domestic violence (DV) is still a significant public health problem, especially in women's health. Few studies have reported the prevalence and domestic violence in Indonesia. The aim of this study was to identify the prevalence, type of violence, and forensic examination on domestic violence victims in emergency departments. Methods: This study was a retrospective analysis of domestic violence victims observed in the Emergency Department at the Bhayangkara Hospital, Pekanbaru, Indonesia, between 2010 and 2014. The determinations of DV cases are based on the medico-legal reports (visum et repertum) and the policeâs official inquiry letters. Results: Out of 6,876 medico-legal injury reports of living victims were reviewed, and 755 (10,9%) cases were DV. The majority of victims in DV were women (93.8%) with childbearing age group as the highest frequency (77.9%). Most of the DV victims were housewives (67.0%). Moreover, physical assault was the most common DV types (98.7%). Bruise was the predominant type of wound among the DV victims (76.2%), and almost half of the victims had abrasions (48.1%). Head and limbs were the predominant sites of wound. Blunt injury was found in more than three-quarters of the victims (88.5%). Conclusion: The prevalence of domestic violence was high among living victims in the emergency department, with women as the majority of victims.